Probing flexibility in porphyrin-based molecular wires using double electron electron resonance. - Lovett, J; Hoffmann, M; Cnossen, A; Shutter, A; Hogben, H; Warren, J; Pascu, S; Kay, C; Timmel, C; Anderson, H (2009)
A series of butadiyne-linked zinc porphyrin oligomers, with one, two, three, and four porphyrin units and lengths of up to 75 A, have been spin-labeled at both ends with stable nitroxide TEMPO radicals. The pulsed EPR technique of double electron electron resonance (DEER) was used to probe the distribution of intramolecular end-to-end distances, under a range of conditions. DEER measurements were carried out at 50 K in two types of dilute solution glasses: deutero-toluene (with 10% deutero-pyridine) and deutero-o-terphenyl (with 5% 4-benzyl pyridine). The complexes of the porphyrin oligomers with monodentate ligands (pyridine or 4-benzyl pyridine) principally adopt linear conformations. Nonlinear conformations are less populated in the lower glass-transition temperature solvent. When the oligomers bind star-shaped multidentate ligands, they are forced to bend into nonlinear geometries, and the experimental end-to-end distances for these complexes match those from molecular mechanics calculations. Our results show that porphyrin-based molecular wires are shape-persistent, and yet that their shapes can deformed by binding to multivalent ligands. Self-assembled ladder-shaped 2:2 complexes were also investigated to illustrate the scope of DEER measurements for providing structural information on synthetic noncovalent nanostructures.